Protective potential of Carduus marianus extract against p-dimethylaminoazobenzene (pDAB) induced hepatocarcinogenesis in mice through apoptosis induction and antioxidant pathway - Saili Paul; Anisur Rahman Khuda-Bukhsh (Journal of Holistic Integrative Pharmacy)
Objective: In homeopathy, ethanolic extract of Carduus marianus (EECM), is used against various liver disorders including cancer. This investigation aims at evaluating hepatoprotective potential of EECM, if any, against p-dimethylaminoazobenzene (pDAB)-induced hepatocarcinogenesis in mouse models in vivo and elucidating its possible underlying mechanism(s). Methods: Randomized sets of inbred mice were chronically fed with different food regimens for varying periods of time and divided accordingly, 6 mice in each group, into control (Normal I and Alcohol II) and treated groups (III-V); group I: fed Normal diet, group II: Normal diet ​+ ​Alcohol, group III: pDAB ​+ ​Phenobarbital (PB), group IV: pDAB ​+ ​PB ​+ ​Alcohol, group V: pDAB ​+ ​PB ​+ ​EECM. They were sacrificed at day 30, 60, 90 and 120. All routine protocols were deployed for cytogenetical, enzymatic, and histopathological studies. Expressions of B-cell lymphoma 2 (Bcl-2), B-cell lymphoma-extra large (Bcl-xl), Bcl-2 associated X protein (Bax), Cysteine aspartic acid protease-3 (Caspase-3), and Matrix metalloproteinase 9 (MMP-9) were evaluated at day 90 and 120 only. The DPPH free-radical scavenging activity of EECM was estimated to determine the antioxidant properties. Results: No mice of groups I and II developed tumors in liver at any fixation intervals while all mice of groups (III-IV) developed liver tumors at three fixation intervals. But in group V mice, 4 each of 6 mice at 90 and 120 days, did not show tumor nodules in their livers, signifying that feeding of EECM could combat carcinogenesis. EECM reduced genotoxic effects and favorably modulated expression of Caspase 3 and MMP-9 as compared to control. Conclusion: The treatment of EECM clearly demonstrated protective action against pDAB induced hepatocarcinogenesis in mice for delaying tumor progression, decreasing total tumor load and genotoxic effects, and also evidenced by favourable modulations of the apoptotic signal proteins like Bcl2, Bcl-xl. Bax, Caspase 3 and other marker enzymes AST (Aspartate amino transferase), ALT (Alanine amino transferase) etc. However, the molecular mechanism of this protective action still needs to be further elucidated.